PENGARUH PENERAPAN PP NO 23 TAHUN 2018 TERHADAP PENERIMAAN PAJAK, EFEKTIFITAS PENERIMAAN DAN PERTUMBUHAN WAJIB PAJAK DI KPP SEMARANG SELATAN - Dzul Fauzi Auzan; Didik Ardianto (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to examine the analysis of the effect of PPh Final PP No. 23 of 2018 on government tax revenues, effectiveness, and increasing the number of taxpayers at tax office in the South Semarang. The dependent variable in this research is government tax revenue, and the number of taxpayers at tax office in the South Semarang and the independent variable in this research is Government Regulation No. 23 of 2018. The population in this research consists of taxpayers who are registered at KPP Pratama Semarang Selatan for the 2017 and 2019 period. Sampling was carried out using a purposive sampling method which finally got taxpayers who used the special rules of UMKM PP No. 46 of 2013 and PP No. 23 of 2018 in calculating the annual tax. This research uses a qualitative descriptive analysis using official data from the South Semarang Tax Office as the source. The results of this study indicate that the new MSME taxation regulations PP no. 23 of 2018 has a positive effect on increasing the growth of taxpayers, but PP no. 23 of 2018 has a negative effect on the amount of state revenue receipts from the MSME tax sector, and also has a negative impact on the effectiveness of tax revenues. based on the target and realization of MSME tax revenues.